On our susceptibility to external memory store manipulation: examining the influence of perceived reliability and expected access to an external store. - Pereira, April E.; Kelly, Megan O.; Lu, Xinyi; Risko, Evan F. (Taylor & Francis, 2022)
Offloading memory to external stores (e.g., a saved file) allows us to evade the limitations of our internal memory. One cost of this strategy is that the external memory store used may be accessible to others, and thus, manipulated. Here we examine how reducing the perceived reliability of an external memory store may impact participants’ susceptibility to its manipulation (i.e., endorsing manipulated information as authentic). Across two pre-registered experiments, participants were able to store to-be-remembered information in an external store and on two critical trials, we surreptitiously manipulated the information in that store. Results demonstrate that an explicit notification of a previous manipulation, a reduction in perceived reliability, can decrease susceptibility to manipulation of the external memory store.
This is an accepted manuscript of an article published by Taylor & Francis in Memory on April 2022, available at: https://doi.org/10.1080/09658211.2021.1990347
Keywords: memory; recognition; recall; offloading; reliability